(untitled) (Salam International Academic Journal, 2019)
Since Hadith is considered to be the second authentic reference to all Muslims, after Qur’an, Muslims can refer to it at any time and solve their problems in the light of the Qur’an and hadith. As it is famous among us, whatever we value greater, we will keep it good and we will try to maintain it well. If we do care this much about ordinary objects, then we should pay more and more attention to the maintenance of the Qur’an and the Hadith, which are two essential elements of our religion. In the present discussion (the position of the Companions to the Ahl-e-Sunna and their role in narration of Hadith), the companion in deed are the role model in maintenance of Hadith and we can learn even how to maintain Hadith in the current era from them. We observed that companion, worked hard to maintain Hadith, initially they memorized, and then wrote it based on need, and, in the same way, with the passage of time, they used to search for its documents, and reviewing the status of narrators of Hadith. All these indicate the attempts of companions towards maintenance of Hadith. It should be noted that the right of Sunna of Mohammad PBUH over us is its implementation, its adaptation to the context of our own and people’s lives. Companions were the best model in this aspect. In addition, Sahibyat also made efforts in maintenance and publication of Hadith. In the current era, we can consider such characters as a model for our self, and learn from their lives how we should inspire our lives from the Sunna, how should we make it the candle for every darkness and difficulty of our lives, how should we adapt the Sunna In our families, and consider it as core principles and foundation of our families. And afterwards to encourage others towards it, so that Sunna could be the first resort of the people in every case of life. And if we do so, we might have performed our responsibility to the Sunna